MiR-122-5p attenuates endothelial-to-mesenchymal transition induced by oxygen and glucose deprivation/reperfusion - Yu, Haiyan; Xu, Jinqiu; Zhu, Pengyin; Zhang, Chunyan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Endothelial-to-mesenchymal transition (EndoMT) is a common phenomenon in vascular diseases, while the role of endothelial dysfunction in central vascular disease remains to be further investigated. MiR-122 is an inflammation-associated non-coding RNA that participates in multiple human disease, but whether miR-122 plays as a critical role in EndoMT induced by ischaemic stroke is unknown. Although BAI2 is known as a brain-specific inhibitor protein of angiogenesis, few studies of BAI2 examined EndoMT. This study investigated the mechanism of EndoMT and the miR-122/BAI2 axis in oxygen-glucose deprivation/reperfusion (OGD/R)-mediated EndoMT. A transient middle cerebral artery occlusion (tMCAO) model and OGD/R treatment were used to mimic the ischaemia-reperfusion injury. The colocalization of CD31 and α-SMA was elevated in the peri-infarct area of tMCAO mice. The expression of miR-122 was decreased in the peri-infarct area of tMCAO mice. Downregulation of miR-122, Occludin, and ZO-1 was observed in human brain microvascular endothelial cells (HBMECs) after OGD/R treatment, while α-SMA expression was increased in HBMECs after OGD/R treatment. MiR-122 overexpression reduced the decrease of Occludin and ZO-1 expression and the increase of α-SMA expression induced by OGD/R. MiR-122 negatively regulated BAI2 expression, and OGD/R treatment enhanced BAI2 expression. Knockdown the expression of BAI2 suppressed the decrease of Occludin and ZO-1 expression and the increase of α-SMA expression induced by OGD/R. In conclusion, miR-122 overexpression attenuates OGD/R-mediated EndoMT by targeting BAI2.